ANALISIS SOSIAL MASYARAKAT INDONESIA DALAM SASTRA CYBER EDISI 2016 - Syifaul Fithriyah (EDU-KATA, 2020)
Research aimed at (1) explaining family social problems, (2) describing social problems of society, and (3) representing social problems in cyber literature in the 2016 edition of Short Story Sunday Newspaper. The method used in this study is qualitative because the research here the source of the data is a literary text sourced from the short stories of the short story of the Koran Sunday 2016. From the data the authors formulated the problems: family social problems, social problems of the community, and social problems of the country. Many of the problems illustrated in the 2016 Newspaper Short Story tell of family conflicts such as conflicts between female candidates, parents and children, community relations: neighboring harmonization, caring friendships, to social events that arise in the country such as the circulation of drugs, gambling, imaging of our higher-ups.